Strategic planning and remuneration - G. S. Andrews (South African Journal of Business Management, 1986)
Management thought, practice and process have changed dramatically over the recent past and we need new ways to think about how business performs and how to measure the managers who run our business operations. With rapidly changing markets, technologies, customers, suppliers and consumers, more and more emphasis is being placed on thinking strategically and on how to position the business for the future. Unfortunately many firms are still grappling with the concept of strategy and do not fully understand the concept of strategic management. As a result, many managers are being encouraged by the reward and compensation system to act in their own interests and not in the company's interests. Poorly designed measurement and compensation systems tend to reward short-term thinking and do not recognize the value of strategic compensation systems. Managers must be made partners in a firm's success by linking compensation to the strategic variables of success.
Keywords: 650